Pendampingan Asertif Terhadap Remaja Korban Pelecehan Seksual di DPPPA Palembang - Afin Fahreza (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The increasing incidence of sexual harassment against adolescents, including sexual harassment against adolescent girls, highlights the need to protect adolescents. Sexual crimes against adolescents are a form of violence committed by adults to satisfy their sexual desires. Sexual violence includes sexual exploitation in the form of prostitution or pornography, fondling, forcing adolescents to touch another person's genitals, sexual intercourse, rape, sexual intercourse with another person same blood (incest) and sodomy. The method used specifically is a very assertive counseling approach, which seeks to support clients who have experienced sexual violence by giving them the space to express their rights, thoughts, feelings, and beliefs directly, honestly and respectfully. Results from mentoring activities suggest that mentoring programs aimed at increasing the self-confidence of victims of sexual harassment can influence victims' behavior, for example by making them confident and courageous in social interactions with the opposite sex and the environment.